Analysis of transcriptomic changes that occur following loss of DARPP-32 expression in breast cancer - Storr, Sarah (2022)
Background Breast cancer is the most common cancer in the UK, with >55,000 new cases per annum and >11,500 deaths, with metastasis the major cause of mortality. Since the early 1990s, the incidence of breast cancer has increased by 18% in the UK with cases predicted to rise 2% between 2014 and 2035. The molecular basis that underpins cancer progression and metastasis is complex and presents an important research challenge. Dopamine and cAMP-regulated protein phosphatase (DARPP-32) is a central signalling switch in the brain and the consequence of altered phosphorylation has been extensively studied. In breast cancer, we have demonstrated that low expression of DARPP-32 is associated with poor clinical outcome of patients; however, the mechanism by which DARPP-32 exerts this effect remains unclear.